Advancements in Microfluidic Cassette-Based iMiDEV™ Technology for Production of L-[11C]Methionine and [11C]Choline - Hemantha Mallapura; Laurent Tanguy; Samin Mahfuz; Lovisa Bylund; Bengt Långström; Christer Halldin; Sangram Nag (Pharmaceuticals, 2024)
Microfluidic technology is a highly efficient technique used in positron emission tomography (PET) radiochemical synthesis. This approach enables the precise control of reactant flows and reaction conditions, leading to improved yields and reduced synthesis time. The synthesis of two radiotracers, L-[11C]methionine and [11C]choline, was performed, using a microfluidic cassette and an iMiDEVTM module by employing a dose-on-demand approach for the synthesis process. We focused on optimizing the precursor amounts and radiosynthesis on the microfluidic cassette. L-[11C]methionine and [11C]choline were synthesized using a microreactor filled with a suitable resin for the radiochemical reaction. Trapping of the [11C]methyl iodide, its reaction, and solid-phase extraction purification were performed on a microreactor, achieving radiochemical yields of >80% for L-[11C]methionine and >60% for [11C]choline (n = 3). The total synthesis time for both the radiotracers was approximately 20 min. All quality control tests complied with the European Pharmacopeia standards. The dose-on-demand model allows for real-time adaptation to patient schedules, making it suitable for preclinical and clinical settings. Precursor optimization enhanced the cost efficiency without compromising the yield. The importance of dose-on-demand synthesis and optimized precursor utilization to produce L-[11C]methionine and [11C]choline was emphasized in this study. The results demonstrated the feasibility of dose-on-demand adaptations for clinical applications with reduced precursor quantities and high radiochemical yields.